Academic Senate Minutes 2010-10-28 - Academic Senate:::::::::
Chair Report. Agenda amended and approved. Minutes of 9/30/10 approved. Revision to the Financial Management concentration – Approved. Revision to the Finance concentration – Approved. Resolution on the Early Start Program approved. Provost Report. Chair-Elect Report. Associated Students Report. JCAP Report and Discussion. Early Start Program Report. Report from the Director of Diversity and Inclusive Excellence. Revision to the Learning Objectives A & C approved. Vice President of Administration and Finance Report. Good of the Order.